Novel approaches for the design, delivery and administration of vaccine technologies - Wallis, J; Shenton, D; Carlisle, R (2019)
It is easy to argue that vaccine development represents humankind's most important and successful endeavour, such is the impact that vaccination has had on human morbidity and mortality over the last 200 years. During this time the original method of Jenner and Pasteur, i.e. that of injecting live-attenuated or inactivated pathogens, has been developed and supplemented with a wide range of alternative approaches which are now in clinical use or under development. These next-generation technologies have been designed to produce a vaccine that has the effectiveness of the original live-attenuated and inactivated vaccines, but without the associated risks and limitations. Indeed, the method of development has undoubtedly moved away from Pasteur's three Is paradigm (isolate, inactivate, inject) towards an approach of rational design, made possible by improved knowledge of the pathogen-host interaction and the mechanisms of the immune system. These novel vaccines have explored methods for targeted delivery of antigenic material, as well as for the control of release profiles, so that dosing regimens can be matched to the time-lines of immune system stimulation and the realities of health-care delivery in dispersed populations. The methods by which vaccines are administered are also the subject of intense research in the hope that needle and syringe dosing, with all its associated issues regarding risk of injury, cross-infection and patient compliance, can be replaced. This review provides a detailed overview of new vaccine vectors as well as information pertaining to the novel delivery platforms under development.